Understanding What Lies Behind Public Bad Leadership In the Federal Government of Somalia - Hashi, Mohamed Bile; Barasa, Tiberius (2022)
This study investigates what lies behind public bad leadership in Somalia's federal government by analysing the perspectives of 21 respondents including senior policy analysts, senior government officials, and representatives of the NGOs, local communities, the youth, religious leaders, and scholars. The key findings of this study are that bad leadership in Somalia manifest in those who operate the federal system against society's needs, lack a clear vision and purpose, put their personal interests ahead of the public interest, dictate what they want to the community, have no prior experience in politics or federalism, and sign unverified deals with foreigners are viewed as bad leaders. Favoritism, clan-based recruitment in government institutions, dictatorship, rapid property creation, short-sightedness, lack of vision, and corruption are major behaviors and activities exhibited bad leadership in Somalia. This study concludes that bad leadership is a fundamental contributor in Somalia's political collapse. Therefore, the study suggests certain measures that may be implemented to address the problem of bad leadership in Somalia including reforming the electoral system, finalizing the provisional constitution, boosting civic education, and thoroughly examining individuals' biographies before allowing them to run for public office.